1994
DOI: 10.2165/00002018-199410060-00002
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Nondepolarising Neuromuscular Blocking Agents

Abstract: Nondepolarising muscle relaxants block neuromuscular transmission, acting as antagonists of the nicotinic receptors at the neuromuscular junction. Their undesired effects are frequently caused by interaction with acetylcholine receptors outside this junction, and autonomic cardiovascular effects may result. Other adverse effects include anaphylactic or anaphylactoid reactions, and histamine release. Various disease states may present specific considerations in the use of nondepolarising muscle relaxants. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 276 publications
0
1
0
Order By: Relevance
“…Nondepolarising blocking drugs will be discussed in the next issue of the Journal (Abel et al 1994). In 1954, Beecher and Todd reported that with the advent of neuromuscular blocking agents, anaesthesia-related mortality increased 6-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Nondepolarising blocking drugs will be discussed in the next issue of the Journal (Abel et al 1994). In 1954, Beecher and Todd reported that with the advent of neuromuscular blocking agents, anaesthesia-related mortality increased 6-fold.…”
Section: Discussionmentioning
confidence: 99%